The Rice Cyclin-Dependent Kinase –Activating Kinase R2 Regulates S-Phase Progression - Fabian-Marwedel, Tanja (American Society of Plant Biologists, 2002)
Cyclin-dependent kinases (CDKs) are the central components of eukaryotic cell cycle regulation. Phosphorylation of CDKs at a conserved threonine residue is required for their full activity and is mediated by a CDK-activating kinase (CAK). The CAK R2 from rice belongs to those CAKs that phosphorylate not only CDKs but also the C-terminal domain (CTD) of RNA polymerase II. We showed that R2 is a nuclear protein with increased expression and increased CTD kinase activity in S-phase. Increasing R2 abundance through a transgenic approach accelerated S-phase progression and overall growth rate in suspension cells. In planta, the CTD kinase activity of R2 was induced by a growth-promoting signal. R2 regulation, therefore, may constitute a plant-specific adaptive mechanism that is used to adjust the rate of cell proliferation in response to a changing environment.